Genetic characterization of group-A rotaviruses among children in eastern India during 2014–2016: Phylodynamics of co-circulating genotypes. Issue 45 (23rd October 2019) - Nayak, Mukti Kant; Banerjee, Anindita; Sarkar, Rakesh; Mitra, Suvrotoa; Dutta, Kunal; Ganguly, Nupur; Ghosh, Chandradipa; Girish Kumar, C.P.; Niyogi, Prabal; Panda, Samiran; Dutta, Shanta; Chawla-Sarkar, Mamta
Highlights: Systemic surveillance of rotavirus in children (≤5 years) hospitalized with diarrhea. Rotavirus positively correlates with dehydration, mean hospital stay and vomiting. Dynamicity of rotavirus genotypes among rural and urban settings during 2014–16. Phylogenetic analyses and variation in antigenic epitopes of prevailing strains. Abstract: Background: Group-A human rotaviruses (GARV) are among the major cause of childhood diarrhea worldwide. In lieu of monitoring the circulatory GARV strains and underscoring the burden of GARV related hospitalization, a systematic surveillance was conducted in three hospitals of eastern India. In this hospital-based diarrheal disease surveillance (2014–2016), GARV was the most common cause of acute infantile gastroenteritis. The strains were genotyped and characterized to understand their prevalence and phylodynamics prior to the introduction of vaccine in eastern India. Materials and methods: A total of 3652 stool samples were screened from children (≤5 years) hospitalized with acute diarrhea during 2014–2016. Initial screening for VP6 antigen was done by ELISA. GARV positive samples were genotyped by multiplex semi-nested PCR and DNA sequencing and phylogenetic analyses were based on the capsid proteins VP4 and VP7. Results: Of 3652 samples, 1817 (49.8%) were GARV positive. G1, G2, G3 and G9 in conjunction with P[4], P[6]and P[8]genotypes were seen to co-circulate in the population. A sharp deflection from G1 to G3 occurred since 2016; upsurge of G9 strains was seen in alternate years, whereas G2 strains had a low frequency. All the circulating genotypes depicted a low phylogenetic relatedness to the vaccine strains. Differences in antigenic epitopes of VP4 and VP7 proteins in local strains were seen when compared to the vaccine strains. A significant difference in the degree of dehydration, duration of mean hospital stay and frequency of vomiting/24 h between GARV positive and negative children was evident. Conclusion: The study provides a relevant set of base-line data on high burden of rotaviral gastroenteritis and the varied genotypic diversity among children prior to the introduction of GARV vaccine in this endemic region. Continuous monitoring during post-vaccination era will be required to assess the impact of vaccination in this region.